2022
DOI: 10.1177/13684302221123922
|View full text |Cite
|
Sign up to set email alerts
|

The influence of team cultural value orientations on norms of conduct in hybrid teams: Implications for team cohesion and performance

Abstract: We advance team composition research by adopting a team-norms perspective to examine the effects of team members’ cultural value orientations—collectivism and uncertainty avoidance orientation—on team functioning and performance in hybrid teams (i.e., teams combining face-to-face and mediated communication). Using data collected at three points in time from a sample of self-managing project teams, results support our proposed theoretical model. Team members’ mean level of collectivism and uncertainty avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 115 publications
1
1
0
Order By: Relevance
“…Team social norms were found to have a significant positive effect on team cohesion (Hypothesis 3 was accepted). Hill et al [ 47 ] studied 209 students, reporting that the interaction between team virtuality and norms increases team cohesion, supporting the results of this study. As a result of a study of 118 soccer players, Høigaard et al [ 60 ] found a significant relationship between norms and cohesion.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Team social norms were found to have a significant positive effect on team cohesion (Hypothesis 3 was accepted). Hill et al [ 47 ] studied 209 students, reporting that the interaction between team virtuality and norms increases team cohesion, supporting the results of this study. As a result of a study of 118 soccer players, Høigaard et al [ 60 ] found a significant relationship between norms and cohesion.…”
Section: Discussionsupporting
confidence: 85%
“…Hill et al [ 47 ] argued that team members should play an important role in determining behavioral norms because they are influenced by cultural value orientations. This study emphasizes that an individual’s internalization of a team’s expectations and values can influence their behavior.…”
Section: Introductionmentioning
confidence: 99%
“…They provided a more differentiated picture of the cohesiveness-efficiency relationship as a number of specific variables were taken into account, namely type of groups, type of tasks, level of analysis of cohesion, criteria and methods for assessing group effectiveness, etc. In addition to cohesion, researchers paid attention (although much less frequently) to group norms, such as performance norms [12]; norms of conduct [13]; cooperative norms [14]; sociability norms [15]; collectivistic norms [16]; and risk-taking norms [17], all as predictors of performance of work groups. Among them, productivity norms (also known as performance or task norms) should be especially highlighted.…”
Section: Introductionmentioning
confidence: 99%